Proposals of the Pinsk District Nobleman Teodor Rodziewicz Regarding the Improvement of the Activities of the Nobility Courts in the Grand Duchy of Lithuania (Late 18th Century) - Stankevič, Adam (Teisė, 2020)
This article analyzes the project for the improvement of the activities of the nobility (land, castle, border, arbitral tribunal and the Supreme Tribunal of Lithuania) courts of the Grand Duchy of Lithuania prepared by Teodor Rodziewicz, a nobleman of the Pinsk district, having the title of cup-bearer. The aim is to reveal the main reasons for the flawed activities of the nobility courts, as singled out by the author of the manuscript, and to discuss his suggestions, which were aimed at remedying this situation. The most important postulates of the judicial reform proposed by T. Rodziewicz were the following: general election of judges, introduction of the fixed terms of office for judges, extension of the areas of responsibility of judges, and collegial examination of cases. Some of these principles were implemented in the Four-Year Sejm.